"Don't Tell My Father": Important Lessons Learned Through EFL Classroom Small Talk - Gabriela Ayala González; Miguel Adrián Leonel de Cervantes Orozco; Víctor Daniel González Cabrera; Faviola Romero Mayoral; Gerrard Edwin Mugford Fowler (Universidad Nacional de Colombia, 2011)
All too often phatic communion is neglected in the English as a foreign language classroom or relegated to the level of formulaic language which merits little or no attention. In this article we argue that phatic communion plays an important role in establishing, developing and maintaining interpersonal relationships between teacher and learners which can be seen in terms of solidarity and supportiveness. Furthermore, small talk offers one of the few opportunities for students to engage in meaningful communicative interaction in the English as a foreign language classroom which is largely characterised by non-authentic language activities. Using classroom data, we attempt to show that teachers and students actively look for ways to enhance personal relationships as they boost the face of other interactants.